Analisis Percepatan Waktu Dan Biaya Proyek Konstruksi Dengan Penambahan Jam Kerja (Lembur) Menggunakan Metode Time Cost Trade Off : Studi Kasus Proyek Pembangunan Prasarana Pengendali Banjir - Priyo, Mandiyo; Sumanto, Adi (Semesta Teknika, 2016)
Time and cost have significanteffect on the success and failure of the projects.Thebenchmark for the success project is usually seen by short finishing time with theminimum cost without leaving the quality.Project management systematically isrequired to ensure the project implementation time in accordance with the contractor even faster so the cost can provide benefits, and also avoid the penalty due todelay in the completion of project. The aim of this research is to calculate thechanges of the cost and (overtime) and to compare the results between the cost ofpenalty cost with the changes after adding the overtime.The secondary dataobtained from the contractor.Data analysis in this research is using MicrosoftProject 2007 program and methods of time cost trade off. The results of theprogram Microsoft Project 2007 is the critical path and the results of the method oftime cost trade off is duration acceleration and cost increases due to the accelerationof the duration in any activities that increased.The results of this study indicate that:(1) From the time cost trade off with the addition of 1 hours of work per dayconducted on first day on critical jobs during the project, obtained the reduction inthe duration of 57 days, from the normal duration of 196 days to 139 days with atotal project cost changes from the normal cost of Rp 16,371,654,833.56 to Rp 16133 .588.292,57 (the difference between the cost of Rp. 238,096,540.99) as well ascausing an increase in the direct cost of Rp 15,469,452,846.76 to Rp15,493,731,373.36 (the difference between the cost of Rp. 24,278,526.60) andindirect costs experienced a decrease of US 902,201,986.80 to Rp 639,826,919.21(the difference between the cost of Rp. 262,375,067.59), (2) cost of accelerating theduration of the project with overtime is cheaper than the cost to be incurred ifprojects experienced delays and penalty.